Dabigatran etexilate for the treatment of acute venous thromboembolism in children (DIVERSITY): a randomised, controlled, open-label, phase 2b/3, non-inferiority trial - Halton, Jacqueline; Brandão, Leonardo R; Luciani, Matteo; Bomgaars, Lisa; Chalmers, Elizabeth; Mitchell, Lesley G; Nurmeev, Ildar; Sharathkumar, Anjali; Svirin, Pavel; Gorbatikov, Kirill; Tartakovsky, Igor; Simetzberger, Monika; et al. (The lancet. Haematology, 2021)
Background - Dabigatran etexilate is a direct oral anticoagulant with potential to overcome the limitations of standard of care in children with venous thromboembolism. The aims of this clinical trial were to study the appropriateness of a paediatric dabigatran dosing algorithm, and the efficacy and safety of dabigatran dosed according to that algorithm versus standard of care in treating children with venous thromboembolism. - Methods - DIVERSITY is a randomised, controlled, open-label, parallel-group, phase 2b/3 non-inferiority trial done in 65 centres in 26 countries. Standard of care (low-molecular-weight heparins, unfractionated heparin, vitamin K antagonists or fondaparinux) was compared with a paediatric oral dabigatran dosing regimen (an age-adjusted and weight-adjusted nomogram) in children younger than 18 years with acute venous thromboembolism initially treated (5-21 days) with parenteral anticoagulation, requiring anticoagulation therapy for at least 3 months. Patients were randomised 1:2 (standard of care:dabigatran) and stratified by age (12 to <18 years, 2 to <12 years, and birth to <2 years) via interactive response technology. The primary composite efficacy endpoint (intention-to-treat analysis) was the proportion of children with complete thrombus resolution, and freedom from recurrent venous thromboembolism and venous thromboembolism-related death. A non-inferiority margin of absolute differences of 20% was used. Secondary endpoints included safety (determined by major bleeding events [time-to-event analysis on the treated set]), and pharmacokinetic-pharmacodynamic relationships (descriptive analyses). This trial is registered with ClinicalTrials.gov, NCT01895777 and is completed. - Findings - 328 children were enrolled between Feb 18, 2014, and Nov 14, 2019. 267 were randomly assigned (90 [34%] to standard of care and 177 [66%] to dabigatran) and included in the analyses. Median exposure to standard of care was 85·0 days (IQR 80·0-90·0) and to dabigatran was 84·5 days (78·0-89·0). Similar proportions of children treated with standard of care and dabigatran met the composite efficacy endpoint (38 [42%] of 90 vs 81 [46%] of 177; Mantel-Haenszel weighted difference, −0·04; 90% CI −0·14 to 0·07; p<0·0001 for non-inferiority). On-treatment bleeding events were reported in 22 (24%) of 90 children receiving standard of care and 38 (22%) of 176 children receiving dabigatran (hazard ratio [HR] 1·15, 95% CI 0·68 to 1·94; p=0·61); major bleeding events were similar between the groups (two [2%] of 90 and four [2%] of 176; HR 0·94, 95% CI 0·17 to 5·16; p=0·95). Pharmacokinetic-pharmacodynamic curves showed a linear relationship between total dabigatran plasma concentration and diluted thrombin time and ecarin clotting time, and a non-linear relationship with activated partial thromboplastin time; curves were similar to those for adults. Serious adverse events were reported for 18 (20%) of 90 children receiving standard of care and 22 (13%) of 176 children receiving dabigatran. The most common severe adverse events were vascular disorders (standard of care three [3%] of 90, dabigatran two [1%] of 176), and gastrointestinal disorders (standard of care two [2%] of 90 and dabigatran five [3%] of 176). One on-treatment death occurred in the standard of care group (retroperitoneal bleeding, not considered treatment related by the study investigators). - Interpretation - An age-adjusted and weight-adjusted dabigatran dosing algorithm was appropriate in children aged birth to less than 18 years with venous thromboembolism. Dabigatran was non-inferior to standard of care in terms of efficacy, with similar pharmacokinetic-pharmacodynamic relationships as those seen in adults, and might be a suitable alternative to standard of care. - Funding - Boehringer Ingelheim.